Etnobotani Tumbuhan Pangan pada Upacara Pernikahan Adat Simalungun - Ropianza Purba; Jamilah Nasution; Rahmiati Rahmiati; Riyanto Riyanto (Universitas Medan Area, 2026)
The use of food plants in traditional ceremonies represents a form of local knowledge that reflects the close relationship between communities and the biological resources in their environment. Among the Simalungun ethnic community, various food plants are still utilized in traditional wedding ceremonies; however, scientific documentation regarding their use remains limited. This study aimed to identify the food plant species used in Simalungun wedding ceremonies, determine the plant parts utilized and their sources, and explore their cultural significance. The research was conducted in Silimakuta District, Simalungun Regency, North Sumatra, using a qualitative descriptive approach through observation, interviews, and documentation involving 36 purposively selected informants. The results revealed that 24 food plant species belonging to 13 families were used in the ceremonies. The most frequently utilized families were Zingiberaceae and Liliaceae. The plant parts used included fruits (25%), tubers (21%), seeds (17%), rhizomes (12.5%), leaves (12.5%), stems (8%), and flowers (4%). Food plants were obtained from farmlands (46%), traditional markets (46%), and home gardens (8%). Traditional dishes such as dayok nabinatur and ikan mas arsik carry symbolic meanings related to harmony, togetherness, and the cultural identity of the Simalungun people. This study demonstrates the important role of food plants in preserving cultural traditions and local ethnobotanical knowledge.